A qualitative study of disengagement in disadvantaged areas of the UK: 'You come through your door and you lock that door'. (July 2018) - Romeo-Velilla, M.; Ellis, N.; Hurst, G.; Grogan, S.; Gidlow, C.
Abstract: Health inequalities are a major concern in the UK. Power imbalances are associated with health inequalities and should be challenged through health promotion and empowering strategies, enabling individuals who feel powerless to take control over their own life and act on the determinants of health (Green and Tones, 2010). This study aimed to explore resident expectations of a community engagement programme that intended to empower communities to take action on pre-identified priorities. The programme targeted communities in deprived areas of a mid-sized city in the UK. A qualitative design was implemented. In-depth semi-structured interviews were undertaken with 28 adult residents at the start of the programme. Transcripts were analysed using an inductive approach to thematic analysis. Resident expectations were explored from a constructivist epistemological perspective. The qualitative inductive approach allowed a second research question to develop which led this paper to focus on exploring how disempowerment was experienced by individuals before taking part in a community engagement programme. Analysis of interviews revealed a 'process of deterioration' that provided insight into how communities might become (more) disadvantaged through disempowerment. Five master themes were identified: external abandonment at the institutional-level (master theme 1); a resulting loss of sense of community (master theme 2); this negatively affected psychological wellbeing of residents (master theme 3); who adopted coping strategies (e.g., disengagement) to aid living in such challenging areas; (master theme 4); disengagement further perpetuated the deterioration of the area (master theme 5). Distrust was identified as a major barrier to participation in community engagement programmes. Overall, our data suggested that community engagement approaches must prioritise restoration of trust and be accompanied by supportive policies to mitigate feelings of abandonment in communities. Highlights: Institutional-level disempowerment can explain community disengagement and distrust. Social isolation can evolve as a coping strategy to deal with life in disadvantaged areas. Restoring trust on professionals and statutory organisations should be the first priority of community engagement programmes.